PERAN GURU AQIDAH DALAM MENINGKATKAN SELF CONTROL REMAJA (Study Kasus di MTs Al Khairiyah Kalodran Serang) - Eni Nur’aeni (Sekolah Tinggi Pariwisata Mataram, 2022)
Aqidah Akhlaq teachers at an education level are highly expected figures in the personal formation of adolescents, in general they occupy junior high school/MTs level and they tend to experience situations where self-control is still indecisive and lacks a sense of responsibility to themselves. The formulation of the problem in this study is as follows: 1. What is the role of aqidah teachers in improving adolescent self-control? 2. What is the condition of self-control in MTs Al-Khairiyah Kalodran students? The aims of this study are: 1.To describe the role of Aqidah Akhlak teachers in improving adolescent self-control in students of Mts Al Khairiyah Kalodran 2. To determine the condition of adolescent self-control in students at Mts Al Khairiyah Kalodran.The methodology that the author uses is a descriptive qualitative methodology with data collection through observation, interviews and documentation. The results of this study: 1. Aqidah akhlaq teachers have a very important role in improving adolescent self-control in students of Mts Al Khairiyah Kalodran. 2. The condition of self-control of students shows a fairly good behavior which previously had a disgraceful attitude. However, after the Akidah akhlaq teacher gave intensive calling and guidance steps, gradually the students of Mts Al Khairiyah Kalodran did not feel indecisive and had an attitude of full responsibility.